De frie teatergrupper i Island i kulturpolitisk perspektiv - Anna Margrét Bjarnadóttir 1977- (2009)
Ritgerðin er skrifuð við Institut for Æstetiske fag, Afdeling for Æstetik og Kultur, Aarhus Universitet The purpose of this thesis is to analyse the cultural political status of the independent theatres in Iceland but cultural political research centred on Iceland is very scarce. The analysis is focused on a few elements: Firstly, the goals of theatre policy in Iceland. Secondly, the Icelandic cultural model is positioned with regards to Chartrand and McCaughey’s (1989) cultural policy models, using the theatre as a reference point. Finally, there is a cultural economical analysis of the independent theatres based on the economic development in Iceland and the evolution of public expenses and private sponsorships to theatres. The analysis concludes that cultural policymaking with clear goals for public involvement with other agents within the cultural sector is very recent and that it has not yet extended to the government’s interaction with independent theatres. The government’s main focus is on the central cultural institutions, e.g. the National Theatre, not grass root movements. The analysis finds that Iceland’s cultural model is best described using Chartrand and McCaughey’s (1989) architect model as the country has a cultural department within the government responsible for cultural policymaking, the arm’s length principle is used extensively and formal public sponsorships are in place for individual artists. Nevertheless, some reservations have to be made in this categorisation of the Icelandic cultural model. Iceland’s public cultural expenses are high in international comparison and private cultural sponsorships increased dramatically during the economic expansion in 2003-2007. The analysis shows that independent theatres only receive around 1% of the government’s support to the cultural sector and some evidence is provided that a majority of private sponsorships go to well-known cultural institutions that already receive extensive public support. The cultural economic position of the independent ...